Characteristics of Phthalates in the Indoor Air of Computer Classrooms - Chang, Feng-Hsiang; Chiu, Chun-Fu (Asian Journal of Chemistry, 2014)
We evaluated the airborne phthalate concentrations inside and outside of two computer classrooms and one office located on a Taiwanese college campus. The four phthalates with the highest median concentrations in indoor air were diisobutyl phthalate (DIBP, 2012.5 ng/m3), di-n-butyl phthalate (DBP, 329.4 ng/m3), di-2-ethylhexyl phthalate (DEHP, 167.6 ng/m3) and diethyl phthalate (DEP, 149.6 ng/m3). Only DBP was detected in the outdoor air, with a median concentration of 174.3 ng/m3. The reference outdoor DBP concentrations were approximately 3-100 times lower than the present indoor DBP concentration results. This strongly indicates that the emission sources were present in the indoor environment. Furthermore,when personal computers were turned on, the concentrations of DEP, DBP, DIBP and DEHP in the indoor air increased and DEHP was a note worthy characteristic phthalate. Opening the doors and windows immediately after entering a computer classroom and decreasing the indoor particle concentrations are both suggested to reduce the exposure of users to DEHP.